Synthesis and Identification of Zinc Oxide Nanoparticles as Precursor for Getting Zinc-Based Biologically Active Additives - S.L. Larin; E.Y. Orlov; N.A. Borsch; L.A. Gorbacheva; E.V. Budko; A.A. Khabarov (Журнал нано- та електронної фізики)
Zinc oxide nanoparticles were synthesized in order to get biologically active additive for correction of zinc-deficiency states. Nanosized zinc oxide was derived by through condensation method from zinc acetate and lithium hydroxide dissolved in dehydrated alcohol. Resulted particles were examined through method of small-angle X-ray scattering. Measurement results confirm presence of nanoparticles with average size about 2 nm.